PENULISAN KITAB AL-JAMIâ AL-AZHAR FI HADITS AN-NABI AL-ANWAR KARYA AL-MANAWI - Daud, Ilyas (Al-Ulum, 2011)
Sejarah penulisan hadis dan ilmu hadis telah melewati serangkaian fase historis yang sangat panjang. Tulisan ini mengkaji secara khusus alah satu kitab Hadis yaitu kitab hadis al-JamÃ®â al-AzhÃ¢r fÃ® HadÃ®ts an-Nabi al-AnwÃ¢r Karya Imam al-Manawi. Tulisan ini menunjukkan bahwa Imam al-Manawi sebagai seorang ulama terkemuka mengumpulkan hadis-hadis nabi dalam hadis al-JamÃ®â al-AzhÃ¢r fÃ® HadÃ®ts an-Nabi al-AnwÃ¢r dan menulisnya dengan menggunakan metode dan sistematika susunan hadis berdasarkan susunan abjad hijaiyah. Hal ini bisa dilihat pada fuhras/indeks kitab setiap juz dari kitab hadis al-JamÃ®â al-AzhÃ¢r fÃ® HadÃ®ts an-Nabi al-AnwÃ¢r. Temanya pun beragam, seperti tauhid, ibadah, akhlak dan hukum. Dalam kitab ini pula al-Imam al-Manawi memuat semua jenis kualitas hadis, baik hadis shahih, hadis hasan, maupun hadis dhaif. Â -----------------The history of writing and science of hadith have passed a series of very long phase. This paper examines one of the hadith books, i.e. Hadith al-Jami al-Azhar Hadith an-Nabi by the Imam Anwar al-Manawi. This paper shows that al-Manawi is an eminent scholar who collected the prophet Muhammadâs tradition in his book al-Jami fi al-Azhar al-Hadith al-Nabi al-Anwar and wrote by using various methods and systematical arrangement of traditions based on alphabetical arrangement. This can be seen in indexes (fuhras) book chapters from each book al-Jami fi al-al-hadits al-Anwar of the Prophet. The theme also varied, such as monotheism, worship, morals and law. In this book al Manawi also mentioned about quality of the Prophetâs traditions, both valid hadith, good (hasan) hadith, or false traditions (dhaif).